Facing Storm: Context of Vulnerability of Marginalized People in Thai-Isan Urban Areas during COVID-19 - Chamaratana , Thanapauge; Prabnok , Puttharak; Jearviriyaboonya , Jakkrich; Meekaew , Nattapon; Phatchaney , Kritsada (Journal of Ecohumanism, 2024)
This study examines the context of vulnerability of marginalized people in urban area of the Northeastern Thailand during the Covid – 19 pandemics. This study employed a qualitative research methodology to collect data through in-depth interview with the key informants who were marginalized people in urban area of Nakhon Ratchasima Municipality, Khon Kaen Municipality, and Udon Thani Municipality, totaling thirty persons. The study results indicate that the phenomena of marginalized people towards the situation of the coronavirus disease outbreak, including shock, seasonal changes, and trends that occur during the time of the outbreak.